Diterpenes from Grangea maderaspatana. (November 2016) - Chang, Fang-Rong; Huang, Shih-Ting; Liaw, Chih-Chuang; Yen, Ming-Hong; Hwang, Tsong-Long; Chen, Ching-Yeu; Hou, Ming-Feng; Yuan, Shyng-Shiou; Cheng, Yuan-Bin; Wu, Yang-Chang
Abstract: Phytochemical investigation of the ethanolic extract of Grangea maderaspatana led to isolation of gramaderins A–D, together with thirteen known compounds. All isolates were assayed for their anti-inflammatory activities. Consequently, 5, 7-dihydroxy-3, 6, 3′, 4′, 5′-pentamethoxyflavone and 5, 3′-dihydroxy-3, 6, 7, 4′, 5′-pentamethoxyflavone showed significant bioactivities by inhibiting superoxide anion generation. 8-Acetoxy-pentadeca-1, 9 Z, 14-trien-4, 6-diyne-3-ol also demonstrated potent inhibition on elastase release. The gramaderins A/C ( β -alkyl linked γ -lactone) and gramaderins B/D ( α -alkyl linked γ -lactone) co-exist in this plant material, of which the latter derivatives are few in nature. Gramaderins C/D possess a special linear dilactone diterpene skeleton, which never been reported. Graphical abstract: Phytochemical investigation of the ethanolic extract of Grangea maderaspatana led to the isolation of gramaderins A–D. Gramaderins C and D possess a linear dilactone diterpene skeleton. Highlights: Phytochemical investigation on Grangea maderaspatana led to the isolation of gramaderins A–D. Alkyl linked γ -lactone and linear dilactone diterpene derivatives were discovered. Some isolated components inhibit superoxide anion generation and elastase release.